(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
The article explores the terminological system and the significance of terms within the language of law. It delves into the concept, function, and unique characteristics of legal terms, and examines how these terms contribute to the overall structure and understanding of legal language. The discussion highlights the importance of precise terminology in law and its impact on clarity and interpretation within the legal framework.